Vitellogenin and Lachesin knockdown in Rhipicephalus bursa influence in feeding and pathogen acquisition - Antunes, S. (2017)
Rhipicephalus bursa is considered as a multi-host tick being the primary hosts of this species, cattle, sheep and goats. R. bursa is widely distributed in the Mediterranean region and has been described as being involved in the transmission of agents of the genus Anaplasma, Babesia, Theileria, Rickettsia among others, with a known impact on animal health. Control of ticks by vaccination has the advantages of being costeffective, reducing environment contamination and preventing the selection of drugresistant ticks. The major constrain in the development of new anti-tick vaccines is still the identification of effective antigens. The present work studies the influence of tick feeding in gene expression as well as interactions between R. bursa tick and the protozoa B. ovis using silencing of genes by RNA interference (RNAi).